Tinjauan Yuridis terhadap Rancangan Undang-Undang TNI dalam Perspektif Supremasi Sipil dan Negara Hukum - Nango, Hamdan; Waraga, Moh. Suryansyah R.; Moonti, Roy Marthen; Kasim, Muslim A. (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This paper discusses in depth the juridical review of the Draft Law on the Indonesian National Army (RUU TNI), by highlighting two key principles in the Indonesian constitutional system, namely civilian supremacy and the principle of the rule of law. Civilian supremacy places civilian authorities - especially the president and parliament - above military institutions in state policy-making, as a guarantee that military power does not become an autonomous force that can intervene in civilian political and governance processes. In this context, the role of the TNI must be placed proportionally and in accordance with the mandate of the constitution, especially Article 30 of the 1945 Constitution which affirms that the TNI as a means of state defence is subject to state policies and political decisions.Through a normative-analytical approach, this article examines the substance of the TNI Bill, including clauses governing the TNI's main tasks, its involvement in military operations other than war (OMSP), as well as authorities that could potentially have multiple interpretations if not accompanied by strict legal supervision and restrictions. Although this bill appears to respond to global dynamics in modern military governance, a number of provisions in it raise concerns about the imbalance between civilian and military power. If not anticipated with an effective civilian control system and transparent accountability mechanisms, the TNI Bill has the potential to deviate from the principles of the rule of law.